Student assistants as mentor-participants: a case study of distributing leadership in academic co-design education - Troost, Ivar; van den Bosch, Lio J.; Nederlof, Niels; Nazar, Shahin; Wijers, Monica; Bakker, Arthur; Pieters, Toine (Frontiers in Education, 2024)
Student Assistants (SAs) are generally regarded as support to the instructor's teaching agency in a course. This case study assesses SAs taking on the more autonomous role of mentorparticipants in student teams during an advanced bachelor's co-design course, advancing our understanding of distributing leadership within such open-ended educational contexts. We use semi-structured interviews and grounded theory analysis to understand how students, teachers and SAs experienced and responded to this shift in SA role. We conceptualise that SAs combined the qualities of both the instructor in creating and holding space for learning based on their personal experiences (i.e., mentoring) and the student in being a pro-active learner and contributor themselves (i.e., participant). Herein they acted as models for students, redistributing the traditional hierarchy of teaching (with a fixed object and subject of teaching) across course participants (i.e., instructors, SAs and students) and into more nuanced roles (i.e., teaching, coaching, mentoring and facilitating). Taking on this role as SA allowed students to take charge while being closely and safely supported. Moreover, this arrangement nurtured a sense of community: students reported experiencing an atmosphere of trust, informality and closeness. Instructors took a more distant role in this constellation, taking responsibility for formal assessment. We conclude that this rearrangement of roles facilitated students' personal leadership and development, authentic undergraduate research and challenge-based learningand outline course design choices that likely contributed to this.